Nanoparticulate PdZn as a Novel Catalyst for ZnO Nanowire Growth - Rachamim Aron (Nanoscale Research Letters, 2010)
Abstract ZnO nanowires have been grown by chemical vapour deposition (CVD) using PdZn bimetallic nanoparticles to catalyse the process. Nanocatalyst particles with mean particle diameters of 2.6 ± 0.3 nm were shown to catalyse the growth process, displaying activities that compare well with those reported for sputtered systems. Since nanowire diameters are linked to catalyst morphology, the size-control we are able to exhibit during particle preparation represents an advantage over existing approaches in terms of controlling nanowire dimensions, which is necessary in order to utilize the nanowires for catalytic or electrical applications. (See supplementary material <supplr sid="S1">1</supplr>) <suppl id="S1"> Electronic supplementary material <text> The online version of this article (doi:10.1007/s11671-010-9567-4) contains supplementary material, which is available to authorized users. </text> <file name="1556-276X-5-904-S1.docx"> Click here for file </file> </suppl>